2016
DOI: 10.1177/1932296816645118
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Emotion Dysregulation, and Bulimic Symptoms in Youth With Type 1 Diabetes

Abstract: This study evaluated the associations between depressive symptoms, emotion dysregulation and bulimic symptoms in youth with type 1 diabetes (T1D) in the context of the diagnosis and treatment of T1D. Study participants were 103 youth in 2 distinct groups: newly diagnosed (New) or transitioning to pump therapy (continuous subcutaneous insulin infusion [CSII]; "Pump"), who completed questionnaires regarding symptoms of depression, emotion dysregulation, and bulimia. Glycemic control (A1c), height, weight, and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This was a secondary analysis of a one-year observational prospective study conducted at 3 pediatric diabetes centers in the U.S. (23). A total of 103 youth ages 10–17 years were identified and recruited within 10 days of diagnosis of type 1 diabetes (n=58) or insulin pump therapy initiation (n=45).…”
Section: Methodsmentioning
confidence: 99%
“…This was a secondary analysis of a one-year observational prospective study conducted at 3 pediatric diabetes centers in the U.S. (23). A total of 103 youth ages 10–17 years were identified and recruited within 10 days of diagnosis of type 1 diabetes (n=58) or insulin pump therapy initiation (n=45).…”
Section: Methodsmentioning
confidence: 99%
“…Other prevalent causes of IO include injection anxiety, particularly in children ( Young-Hyman et al, 2016 ), and fear of hypoglycaemia (low blood sugar; Wild et al, 2007 ). Diabetes burnout, a state of exhaustion towards the condition associated with lack of treatment adherence and deficient blood glucose control ( Young-Hyman et al, 2016 ), may also result in omission of insulin.…”
Section: Diabetic Ketoacidosis and Mortalitymentioning
confidence: 99%
“…Other prevalent causes of IO include injection anxiety, particularly in children ( Young-Hyman et al, 2016 ), and fear of hypoglycaemia (low blood sugar; Wild et al, 2007 ). Diabetes burnout, a state of exhaustion towards the condition associated with lack of treatment adherence and deficient blood glucose control ( Young-Hyman et al, 2016 ), may also result in omission of insulin. In this instance, people with T1D report feeling both physically and mentally tired of the constant need for self-care ( Abdoli et al, 2020 ) and are therefore unable to manage their diabetes control as adequately as is necessary.…”
Section: Diabetic Ketoacidosis and Mortalitymentioning
confidence: 99%
“…Kafali and colleagues 22 found that DEB was associated with experiencing difficulty accessing emotion regulation strategies and regulating one's emotions. Young-Hyman and colleagues 23 highlighted that the association between depressive symptoms and bulimic symptoms was moderated by emotion dysregulation, such that the interaction…”
Section: Introductionmentioning
confidence: 99%